PHYSICS AND ITS RELATIONSHIP TO SENSE OF SELF AND SOCIAL INTELLIGENCE AMONG FIFTH-GRADE STUDENTS PREPARATION - Prof. Dr. Etimad Naji Fayyad (Scholars Digest Publishing, 2024)
Self-awareness is a complex process that involves a person's awareness of himself and his understanding of his thoughts, feelings, and personal characteristics; this feeling goes beyond mere external perception, to include a deep understanding of who a person is, and how he interacts with and is affected by his surroundings. This ability to be self-aware is one of the main pillars in the development of the individual, as it enables him to evaluate his thoughts and behaviors and work to improve aspects of his personal and social life.
Keywords: Sense of self, social intelligence and their relationship to physics achievement.